VARIETIES OF TOMATO (Lycopersicum esculentum) BY USING LOWER TRUNK INNOVATION - Brianata Rosadhi, Pramono Hadi, Tri Rahayu & (Proceeding of International Congress, 2014)
The research entitled âVarieties of Tomato (Lycopersicum esculentum) by Using Lower TrunkInnovation.â The research aims at knowing the age of switching, varieties of growth, and the highestyield on tomato. This research conducted in October 2013 â December 2014 in Kedunggalar village,District of Ngawi. The method of the research is factorial method by using Randomized Complete Design,which consist of two treatment factors; treatment factor is based on the age of cepokak covering threetreatments and treatment factor is based on varieties of tomato covering two treatments. From those twotreatments, the research finds six combined treatments and each combination of treatment should repeatthree times. The treatment based on the age of switching shows a real affect toward parameter ofsuccessful observation , the amount of shoots, the length of shoots, the amount of flower, fruit, weight offresh fruit, and weight of dried stover. The treatment which based on several varieties shows significantlyreal affect as well toward the success of switching, the amount of shoots, the length of shoots, the amountof flower, the amount of fruit, the weight of fresh fruit, and the weight of dried stover. The interactionboth in the treatment based on the age and varieties show significantly real affect toward the success ofswitching, the amount of shoots, the length of shoots, the amount of flower, the amount of fruit, theweight of fresh fruit, and the weight of dried stover. The result of the research shows that the highest yieldfalls into the weight of fresh fruit based on the treatment of M3V2/six week of tomato switching. Whilethe lowest yield falls into treatment M3V1/six week tomato switching.Keywords: the age of switching, cepokak, types of varieties